2020
DOI: 10.3892/or.2020.7502
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin promotes colorectal cancer cell migration through upregulation of lncRNA MALAT1

Abstract: Colorectal cancer (CRC) is the third most common tumor in the world; however, the role and mechanism of endoplasmic reticulum (ER) stress in CRC metastasis remains largely unclear. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA (lncRNA), which has previously been associated with CRC metastasis. It has been suggested that ER stress pathways regulate lncRNA expression; however, the effect of ER stress on MALAT1 expression in cancer is unknown. The present study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Further studies have shown that activated IRE1 and PERK signaling pathways increase the expression of MALAT1, which promote colorectal cancer (CRC) cell migration. Bioinformatic analysis has indicated XBP1 and ATF4 binding sites within the MALAT1 gene promoter region [ 87 ]. It has been believed that ER stress-regulated lncRNAs play critical roles in tumor progression.…”
Section: Er Stress Regulates Ncrnas Expressionmentioning
confidence: 99%
“…Further studies have shown that activated IRE1 and PERK signaling pathways increase the expression of MALAT1, which promote colorectal cancer (CRC) cell migration. Bioinformatic analysis has indicated XBP1 and ATF4 binding sites within the MALAT1 gene promoter region [ 87 ]. It has been believed that ER stress-regulated lncRNAs play critical roles in tumor progression.…”
Section: Er Stress Regulates Ncrnas Expressionmentioning
confidence: 99%
“…Moreover, in CRC tissue samples, MALAT1 is positively regulated with the X‑box‑binding protein 1 (XBP1) and ATF4 binding sites. Therefore, the IRE1/XBP1 and PERK/ATF4 signaling pathways are involved in MALAT1-induced CRC progression [ 91 ].…”
Section: The Role Of Malat1 In Colorectal Cancermentioning
confidence: 99%
“…Kaempferol, a flavonoid compound with strong anticancer effects, also induce gastric cancer cell death by activating IRE1-JNK-CHOP pathway [32]. However, the activation of IRE1-XBP-1 may enhance the migration ability of colorectal cancer cells and thus promote the progression of colorectal cancer [33]. As for pancreatic cancer, the IRE1α-XBP1 signaling pathway has previously been shown to contribute to pancreatic cancer cell invasion in xenograft models [34].…”
Section: Ire1mentioning
confidence: 99%